Analysis of the impact of circular economy over linear economy in the paper processing industry. (2022) - Sakthivelmurugan, E.; Senthilkumar, G.; Karthick, K.N.
Graphical abstract: Abstract: In the present scenario, the linear economy principles are widely used in all fields. As per the linear economy concern once the product is utilized and treated as a waste. In the future, the raw material requirement plays a vital role in many fields because of the lack of availability of resources. To meet the future demand, we need to focus on new techniques, methodologies, and principles for the effective utilization of resources. Given literature, the linear economy principles are replaced by the circular economy in many sectors. As per the circular economy concern, the waste product is again utilized as an input for making secondary products. In this paper, an attempt is made on the effective utilization of paper waste for making secondary products using circular economy techniques. The 9R model is used for the subjective study of various stages of paper-making processes. In addition to that, the fuzzy DEMATAL method is used for pairwise comparison of the linear economy, circular economy, and paper waste. Further analysis is carried out on how the solid waste and waste heat are treated as an input for making secondary products such as agricultural products, fuel, etc.